Dampak Globalisasi terhadap Pendidikan Islam - Ira Kurnia Putri; Misra Misra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Globalization is a phenomenon that brings major changes in various aspects of life, including in the field of Islamic education. This article aims to examine the impact of globalization on the Islamic education system, the challenges and opportunities faced, and strategies for strengthening Islamic education in the midst of global currents. The research method used is a literature study with a qualitative approach. The results of the study show that globalization has an ambivalent impact on Islamic education, which on the one hand opens wide access to science and technology, but on the other hand brings serious challenges related to moral decline, consumptive culture, and identity crisis among the younger generation. Strategies that can be implemented include prophetic approaches, reinventing the Islamic education system, and supporting institutional transformation and human resources. This research recommends that Islamic education not only survive the globalization, but also be able to play an active role in shaping civilization rooted in Islamic values.